Peran Media Sosial dalam Membangun Citra Merek Global pada Brand Adidas di Indonesia - Joshua Valerio,; Oktavian Tri Pandowo,; Sumando Magnus Siboro, (Jurnal Publikasi Ilmu Manajemen, 2025)
The rapid development of digital technology has significantly transformed how global brands communicate and build relationships with consumers. Social media has become a primary platform enabling interactive, personalized, and two-way communication, making it a strategic tool for shaping global brand image. This study analyzes the role of social media in constructing Adidas’ global brand image in Indonesia. Using a literature review method, the research synthesizes digital marketing theories, global brand image concepts, and empirical findings from national and international studies on social media strategies and consumer behavior. The findings show that social media plays a crucial role in strengthening Adidas’ global brand image in the Indonesian market. Global campaigns such as Impossible Is Nothing and Run for the Oceans effectively reinforce perceptions of Adidas as an innovative, modern, and premium brand. Consistent messaging, visual identity, and exposure to global content enhance brand equity among Indonesian consumers, aligning with Alalwan (2018) and Hidayat & Khairunnisa (2021). Moreover, glocalization emerges as a key strategy, enabling Adidas to integrate global brand values with local preferences. Collaborations with local influencers, engagement with the Adidas Runners community, and localized content strengthen emotional connections while preserving global identity. Overall, social media functions not merely as a promotional medium but as a strategic instrument for developing and sustaining Adidas’ global brand image in Indonesia.